Resting-state brain connectivity correlates of musical sophistication - Cui, Anja-Xiaoxing; Kraeutner, Sarah N.; Motamed Yeganeh, Negin; Hermiston, Nancy; Werker, Janet F.; Boyd, Lara A. (Frontiers in Human Neuroscience, 2023)
A growing body of research has investigated how performing arts training, and more specifically, music training, impacts the brain. Recent meta-analytic work has identified multiple brain areas where activity varies as a function of levels of musical expertise gained through music training. However, research has also shown that musical sophistication may be high even without music training. Thus, we aim to extend previous work by investigating whether the functional connectivity of these areas relates to interindividual differences in musical sophistication, and to characterize differences in connectivity attributed to performing arts training. We analyzed resting-state functional magnetic resonance imaging from n = 74 participants, of whom 37 received performing arts training, that is, including a musical instrument, singing, and/or acting, at university level. We used a validated, continuous measure of musical sophistication to further characterize our sample. Following standard pre-processing, fifteen brain areas were identified a priori based on meta-analytic work and used as seeds in separate seed-to-voxel analyses to examine the effect of musical sophistication across the sample, and between-group analyses to examine the effects of performing arts training. Connectivity of bilateral superior temporal gyrus, bilateral precentral gyrus and cerebellum, and bilateral putamen, left insula, and left thalamus varied with different aspects of musical sophistication. By including these measures of these aspects as covariates in posthoc analyses, we found that connectivity of the right superior temporal gyrus and left precentral gyrus relate to effects of performing arts training beyond effects of individual musical sophistication. Our results highlight the potential role of sensory areas in active engagement with music, the potential role of motor areas in emotion processing, and the potential role of connectivity between putamen and lingual gyrus in general musical sophistication.